Analisis Tingkat Kebisingan Menggunakan Model Calculated of Road Traffic Noise di Area UPN “Veteran” Jawa Timur - Dinayah, Ignacia Putri; Rachmanto, Tuhu Agung (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Each year, universities enroll new students, which increases the use of motorized vehicles. An increase in the number of motorized vehicle users can cause noise impacts around the learning area, which can disrupt the learning process. The data needed is vehicle volume, vehicle speed, and road specifications. The collected data are then processed using the CoRTN model to obtain the noise level. The research was conducted at UPN